2004
DOI: 10.1029/2003wr002919
|View full text |Cite
|
Sign up to set email alerts
|

Assessing denitrification in groundwater using natural gradient tracer tests with 15N: In situ measurement of a sequential multistep reaction

Abstract: Denitrification was measured within a nitrate-contaminated aquifer on Cape Cod, Massachusetts, using natural gradient tracer tests with 15 N nitrate. The aquifer contained zones of relatively high concentrations of nitrite (up to 77 mM) and nitrous oxide (up to 143 mM) and has been the site of previous studies examining ground water denitrification using the acetylene block technique. Small-scale (15-24 m travel distance) tracer tests were conducted by injecting 15 N nitrate and bromide as tracers into a depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 89 publications
6
56
2
Order By: Relevance
“…Among the N removal functions, denitrification activities were found to be significant in submerged soils such as wetlands 38 , riparian zones 7 , and also in groundwater 28 . In the study area, rice paddy soil, which was also known to remove N during the rice growing season through denitrification and plant uptake 5,24,32,33 , was predominant (Table 1).…”
Section: Difference In N Removal Through the Outflowmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the N removal functions, denitrification activities were found to be significant in submerged soils such as wetlands 38 , riparian zones 7 , and also in groundwater 28 . In the study area, rice paddy soil, which was also known to remove N during the rice growing season through denitrification and plant uptake 5,24,32,33 , was predominant (Table 1).…”
Section: Difference In N Removal Through the Outflowmentioning
confidence: 99%
“…However, the method does not answer the questions of how much N derived from nonpoint sources enters the water and when 20 , because those load units are usually determined using only outflow data independently of the amounts of N input on the soil surface; moreover, concerning environmental pollution, it neglects the importance of N removal activities in submerged soil such as rice paddies 5,24,32,33 and wetlands 38 , which are a typical and widespread feature of monsoon Asia, as well as riparian zones 7 and the groundwater system 28 . The N removal activities in a rice paddy are considered as including N uptake by the rice plants, N accumulation in the soil and denitrification in the submerged reducing condition during the growing period paddies are persistently expected, quantitative evaluation on a catchment scale has not been fully achieved yet, because of the lack of an appropriate tool.…”
Section: Introductionmentioning
confidence: 99%
“…That vacuum-flask method was deemed too expensive for the LINX project, but we did employ it to test alternative methods. Other studies have collected water samples by completely filling serum vials and sealing them with thick, plug-type septa, conducting headspace extractions of dissolved gases later in the laboratory (Smith et al 2004. Another, more recently developed approach is the use of membrane-inlet mass spectrometry , but this requires special equipment and works best at greater 15 N enrichments than those attained in the LINX experiments.…”
Section: N Tracer Experimentsmentioning
confidence: 99%
“…Such experiments are often best conducted in situ in the field to avoid artifacts associated with containment of water and sediments in microcosms such as flasks or cores. In-situ experimental additions of 15 N have been employed in a wide range of aquatic ecosystems to study N cycling (Peterson et al 2001, Holmes et al 2000, Tobias et al 2003, Mulholland et al 2004, Smith et al 2004, Gribsholt et al 2005.…”
mentioning
confidence: 99%
“…Their results showed that tidal activity forces the seawater to intrude further inland and also creates a thicker interface. Smith et al [2004] demonstrated that numerical results for SGD are strongly affected by dispersion parameter values set in the aquifer as saltwater intrusion and dispersion determine the dynamics of recirculating seawater discharge. Werner and Lockington [2006] demonstrated that doubling the tidal amplitude caused the width of the salinity distribution to increase, but there was no significant encroachment or lateral movement of the mixing zone.…”
Section: Submarine Solute Transport and Mixing Processesmentioning
confidence: 99%